Pengaruh Pemberian Gaji Terhadap Motivasi Kerja dan Profesionalisme Guru Honor - Juwita Merdja; Stefania Seto (PEDAGOGIKA, 2020)
This study aims to determine the direct effect of salary giving on the motivation and effectiveness of teacher learning in the learning process. The provision of salary is a form of gratitude for the hard work of the teachers in this case honorary staff who have dedicated themselves as teachers. With the provision of salary it will motivate the teacher in the teaching and learning process in the classroom. The population in this study were teachers in Ende district who were included in the voluntary teacher category with salaries obtained based on committees and from school operational assistance or commonly referred to as BOS funds. The research method is a survey research with path analysis approach. Data collection was carried out using a questionnaire, which has been tested. The results of the study showed that there was a positive and significant direct effect on salary giving, and work motivation on teacher professionalism. For this reason, policies are needed to improve teacher professionalism, it is necessary to increase the provision of salaries and work motivation.